Daisy and the trouble with vampires - Gray, Kes; Sharratt, Nick Parsons, Garry (Red Fox London, 2016)
It's Halloween and Daisy is going trick-or-treating for the very first time. In the dark in the fog with a vampire armed only with a torch and some silly string